Мікроанімації в UI: як вони покращують користувацький досвід - Лелюк, О. О. (ХНУРЕ, 2025)
Microanimations are subtle animated elements in user interfaces that enhance UX by providing visual feedback and improving navigation. They make interactions more intuitive and engaging, helping users navigate interfaces effectively. Research shows that microanimations can boost user satisfaction and draw attention to key elements, potentially increasing conversion rates. However, their implementation must be thoughtful, ensuring they are unobtrusive and optimized for performance across devices. Designers should focus on user centered approaches, maintaining consistency and testing animations for smooth functionality. Properly implemented microanimations enhance usability and make digital products more engaging, improving the overall user experience.
Keywords: мікроанімація; користувацький досвід